2016
DOI: 10.4238/gmr.15027669
|View full text |Cite
|
Sign up to set email alerts
|

Th17/Treg cell expression in children with primary nephritic syndrome and the effects of ox-LDL on Th17/Treg cells

Abstract: ABSTRACT.To investigate the role of T-helper cells/Treg (Th17/ Treg) and morbidity factors related to primary nephritic syndrome (PNS) in children, as well as the influence of ox-low density lipoprotein (ox-LDL) on Th17/Treg expression in children with PNS. To clarify the pathogenesis of PNS in children, 50 children with PNS treated in our hospital were enrolled in the study group. Additionally, 20 healthy children who came to our hospital for physical examination during the same period were enrolled in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 27 publications
0
10
0
3
Order By: Relevance
“…The pathogenesis of minimal change disease and the basis for immunosuppressive therapies are unclear. Because studies suggest an imbalance of Th1/Th2 cytokines, 30,31 Th17/Treg dysregulation, [32][33][34][35][36] and abnormalities in B cells, 37,38 we examined the proportions of B and T lymphocyte subsets by flow cytometry in patients receiving MMF or levamisole. Similar to previous reports, we found that disease relapse was associated with Th2 39 and Th17 [33][34][35] up-regulation, and down-regulation of Treg cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis of minimal change disease and the basis for immunosuppressive therapies are unclear. Because studies suggest an imbalance of Th1/Th2 cytokines, 30,31 Th17/Treg dysregulation, [32][33][34][35][36] and abnormalities in B cells, 37,38 we examined the proportions of B and T lymphocyte subsets by flow cytometry in patients receiving MMF or levamisole. Similar to previous reports, we found that disease relapse was associated with Th2 39 and Th17 [33][34][35] up-regulation, and down-regulation of Treg cells.…”
Section: Discussionmentioning
confidence: 99%
“…Because studies suggest an imbalance of Th1/Th2 cytokines, 30,31 Th17/Treg dysregulation, [32][33][34][35][36] and abnormalities in B cells, 37,38 we examined the proportions of B and T lymphocyte subsets by flow cytometry in patients receiving MMF or levamisole. Similar to previous reports, we found that disease relapse was associated with Th2 39 and Th17 [33][34][35] up-regulation, and down-regulation of Treg cells. 34,36 Contrary to reports of Th1 up-regulation with levamisole, 40 and B cell 41 and Th17 42 down-regulation and Treg up-regulation 43 with MMF, we did not find differences in lymphocyte subsets at follow-up evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Нам не удалось найти исследования, прослеживаю-щего изменения уровня Th17 от рождения и до очень пожилого возраста, однако наши данные хорошо корреспондируют с уровнем Th17 в кон-трольных группах в многочисленных исследова-ниях субпопуляции Th17 при различных заболе-ваниях у людей разного возраста [13,19,20,27]. У здоровых детей грудного и младшего возраста Th17 определяются на уровне 1-3% [13,19], а у пожилых людей их количество прогрессивно на-растает с возрастом [27]. Однако сопоставление данных литературы осложняется тем, что в раз-ных работах применяли разные способы детекции Th17-лимфоцитов.…”
Section: таблица 1 состав основных субпопуляций т-лимфоцитов в перифunclassified
“…Многие авторы для анализа баланса иммун-ной системы предлагают использовать отноше-ние Treg/Th17 [13,19,20,27]. Мы провели соот-ветствующие расчеты.…”
Section: таблица 1 состав основных субпопуляций т-лимфоцитов в перифunclassified
See 1 more Smart Citation